2006
DOI: 10.2460/javma.228.6.914
|View full text |Cite
|
Sign up to set email alerts
|

Association of neonatal serum immunoglobulin G1 concentration with health and performance in beef calves

Abstract: By use of likelihood ratios, the threshold of serum IgG1 concentration for optimal health and performance of calves was higher than values reported previously. Implementation and maintenance of management and intervention strategies designed for early detection and treatment of calves at risk for failure of passive transfer will likely result in increases in preweaning health and performance parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 13 publications
6
89
4
1
Order By: Relevance
“…Similar results were reported for dairy heifer calves [18,23,25] , dairy healthy goats [21,22] , beef calves [17,24] and healthy buffalo calves [19] . Our study determined a significant positive linear correlation between SIgG-24 and body weight at day 28 and ADG from birth to day 28 as reported by a single previous study [10] but this study was conducted only 20 healthy lambs.…”
Section: Passive Immunity and Growth Performancesupporting
confidence: 77%
See 2 more Smart Citations
“…Similar results were reported for dairy heifer calves [18,23,25] , dairy healthy goats [21,22] , beef calves [17,24] and healthy buffalo calves [19] . Our study determined a significant positive linear correlation between SIgG-24 and body weight at day 28 and ADG from birth to day 28 as reported by a single previous study [10] but this study was conducted only 20 healthy lambs.…”
Section: Passive Immunity and Growth Performancesupporting
confidence: 77%
“…Recent studies have shown that passive immunity in newborn ruminants [17][18][19][20][21][22] not only helps to prevent disease but also enhances growth performance. However, the relationship between growth performance and passive immunity in lambs was studied for only healthy and small number of lambs (generally <40) and the period generally restricted to neonatal period (first 28 days of life) [10,15,20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Net energy consumption was different between calves on the H, M and L planes of nutrition during the pre-BRD period (P < concentrate does not appear to augment immune function in dairy calves. Passive transfer of maternal immunoglobulin is important in determining the subsequent health and level of morbidity in the pre-weaned calf (Donovan et al, 1998;Dewell et al, 2006;Godden, 2008;Berge et al, 2009;Furman-Fratczak et al, 2011;Lorenz et al, 2011;Murray et al, 2014). However, consistent with other studies (Sivula et al, 1996b;Virtala et al, 1996), the level of maternally derived serum immunoglobulin (measured by the ZST test) did not affect the likelihood of a calf developing BRD during the pre-weaning period in this study.…”
Section: Environmental Measurescontrasting
confidence: 44%
“…Immunoglobulin concentrations in precolostral calves are normally zero or very low; however, the presence of gamma globulins in serum is detectable just a few hours after colostrum intake. Calves that receive insufϐicient colostrum present a minimal increase in immunoglobulin levels in serum (Eckersall 2008), and FPIT is considered when IgG levels are below 800mg/dL 24 hours after birth, while concentrations above 1,500mg/ dL of serum IgG at that time are considered ideal for PIT (Dewell et al 2006, Waldner & Rosengren 2009). In our study, all the animals reached desirable levels of serum IgG through natural suckling.…”
Section: Resultsmentioning
confidence: 99%